2010
DOI: 10.1016/j.ajog.2010.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Levator defects affect perineal position independently of prolapse status

Abstract: Objective Determine the effect of levator defects on perineal position and movement irrespective of prolapse status. Study Design Forty women from an ongoing study were divided into two groups of 20 women with and without severe levator defects. Prolapse status was matched between groups with 50% having stage III or greater anterior wall prolapse. Perineal structure locations were measured against standard axes on MR scans at rest, maximum contraction (Kegel), and maximum Valsalva. Differences in location we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Advanced dynamic imaging is needed to assess movement and function of this structure in live women. While MRI can define the perineal body, the low resolution of dynamic MR limits its usefulness in this regard [5,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advanced dynamic imaging is needed to assess movement and function of this structure in live women. While MRI can define the perineal body, the low resolution of dynamic MR limits its usefulness in this regard [5,9].…”
Section: Discussionmentioning
confidence: 99%
“…Avulsion of the puborectalis muscle, i.e., trauma to the insertion of this muscle on the os pubis, is a common consequence of vaginal childbirth, especially a first vaginal delivery [8]. In an MRI study in women with levator defects, the perineal structures were found to be located more caudally at rest [9]. Since an enlarged hiatal area compromises the support of all pelvic organs, vaginal delivery is likely to increase the mobility of perineal body and anorectal junction.…”
Section: Introductionmentioning
confidence: 99%
“…Two functional characteristics of the LA muscle have been described: its ability to lift (vertically in the standing posture) the pelvic organs, and its action in squeezing the levator hiatus closed (horizontally in the standing position) [14, 15]. It is unclear, at present, how much each component of the levator contributes to each of these two actions.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, a study by DeLancey and Hurd 44 also reported that uroginal hiatus size is related to prolapse size. 47 In this study, MRO images displayed significant elongation in dimensions of H and M lines that was seen in all POP patients in standing and supine positions but not in the control group. We recognize that the ongoing debate over reference lines applied to MRI is a limitation that impacts our study.…”
Section: Cuaj -Original Researchmentioning
confidence: 41%